Oral care tablet containing kiwifruit powder affects tongue coating microbiome. Issue 3 (17th May 2022) - Fukui, Makoto; Asakuma, Hiroki; Horiuchi, Hiroko; Takii, Hiroshi; Yoshioka, Masami; Hinode, Daisuke
Abstract: Objectives: Tongue coating, a kind of biofilm formed on the tongue dorsum, is the cause of various clinical conditions, such as oral halitosis and periodontal diseases, because Fusobacterium nucleatum acts as a bridge between other oral bacteria and periodontopathogenic bacteria in biofilm formation. Our previous clinical study revealed that taking oral care tablets containing kiwifruit powder significantly reduced not only tongue‐coating index and volatile sulfur compounds but also total bacteria and F. nucleatum in tongue coating. In this study, we analyzed the microbiome of tongue coating samples obtained before and after oral care tablets intake to clarify whether this tablet is a useful tool for daily tongue care. Methods: Thirty‐two healthy young adults were enrolled, and a crossover clinical trial was conducted. We instructed subjects to remove tongue coating by tongue brush for intervention I, to keep the oral care tablet containing kiwifruit powder on the tongue dorsum and to let it dissolve naturally for intervention II. Microbial DNA was isolated from the collected tongue coating samples in each subject, then 16S rRNA next‐generation sequencing, operational taxonomic unit clustering, and statistical analysis were performed. Results: The microbiome analysis revealed that the oral care tablet in intervention II prompted a significant change in the tongue microbiota composition, a significant reduction in the relative abundance of Prevotella and Porphyromonas, and an increase in Firmicutes/Bacteroidetes ratio when compared to that in intervention I. Conclusion: These results suggested that the oral care tablet might contribute to the improvement of the oral condition due to its good influence on the tongue coating microbiome.